Update on the Serum Biomarkers and Genetic Factors Associated with Safety and Efficacy of rt-PA Treatment in Acute Stroke Patients - C. Nafría; I. Fernández-Cadenas; M. Mendioroz; S. Domingues-Montanari; M. Hernández-Guillamón; J. Fernández-Morales; A. del Río-Espínola; D. Giralt; L. Deu; P. Delgado; A. Rosell; J. Montaner (Stroke Research and Treatment, 2011)
An accurate understanding of the mechanisms underlying an individual's response to rt-PA treatment is critical to improve stroke patients' management. We thus reviewed the literature in order to identify biochemical and genetic factors that have been associated with safety and efficacy of rt-PA administration after stroke.